Modern Contraceptive Use and Associated Factors In USSA Local Government Area Of Taraba State, Nigeria - Adaki Yohanna Andeskebtso (Journal of Healthcare and Biomedical Science, 2023)
With the high rate of unintended pregnancy in the world, encouraging the use of contraceptives has become necessary. However, some factors may influence whether a woman agrees to utilize contraceptives or not. This paper examines the impact of individual factors, sociocultural factors, and health system factors on the utilization of contraceptives in Ussa Local Government Area of Taraba State, Nigeria. Through a literature-based analysis and the application of rational choice theory, the findings highlight the complex interplay of these factors in shaping contraceptive utilization patterns in Ussa Local Government Area. Individual hurdles to uptake were identified as a lack of information about contraception, socioeconomic status, misconceptions, and unfavorable attitudes. Individuals' decision-making processes are influenced by sociocultural variables such as religion and cultural traditions that oppose contraception. Furthermore, a lack of contraceptive availability, a shortage of skilled healthcare practitioners, and a weaker healthcare infrastructure all restrict access to and utilization of contraceptive therapies. The paper recommended that focused interventions should address these various challenges to boost contraceptive usage in Ussa LGA. Individuals, communities, and religious leaders should be targeted for education and awareness efforts to debunk misunderstandings, enhance knowledge, and encourage favorable attitudes regarding contraception. Engaging community leaders and religious organizations in family planning advocacy can assist transform sociocultural norms in favour of family planning. Improving the availability, price, and quality of contraception, as well as training healthcare practitioners, will be crucial for boosting the utilization of contraceptives.